Edukasi Bahaya Timbal pada Sekolah Rentan Polusi terhadap Prestasi Akademik dan Kesehatan Siswa - Indah Tri Susilowati; Noviana Dewi; Endang Widhiyastuti (Universitas Muhammadiyah Semarang, 2023)
This community service project is a promotive and preventive activity that aims to educate students about the danger of lead exposure accumulation in students, delivered to teaching staff throughout Central Java. This activity was conducted as counseling using the webinar method through zoom meetings. Participants were enthusiastic, as seen from the questions asked during the discussion and question-answer sessions. The ability of participants to answer pretest and posttest questions showed an increase in participants’ knowledge between before and after the counseling. The average score of the pretest was 7.00 with a standard deviation of 3.428, while the average score of the posttest was 14.06 with a standard deviation of 1.983. A paired t-test was then used to determine whether the scores from the pretest and posttest differed. Given that the p-value for the difference between the pretest and posttest scores was 0.000, it can be said that the difference is statistically significant. It can be determined that the partner satisfaction questionnaire's answers were valid because they ranged from 0.549 to 0.905 when it was previously assessed for validity using the Pearson product-moment method. The instrument passed the reliability test with a Cronbach Alpha rating of 0.925, indicating that it was trustworthy. According to the results of the partner satisfaction survey, the typical score was 4.09. Thus, it can be concluded that the activity satisfies the participants. Based on the results of data analysis, it can be said that the counseling activities can increase participants’ knowledge about the danger of lead exposure accumulation on students’ achievement.